2008
DOI: 10.1590/s1516-18462008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Resultados timpanométricos: lactentes de seis meses de idade

Abstract: , Luciana Lozza de Moraes Marchiori(3) RESUMOObjetivo: verifi car os achados timpanométricos em lactentes de seis meses de idade, sendo ou não amamentados com aleitamento materno exclusivo e/ou predominante. Métodos: foram avaliados 46 lactentes que estavam com seis meses na data da avaliação, sendo que 30 (61,22%) lactentes estavam sendo submetidos à amamentação exclusiva por um período mínimo de seis meses e 16 (34,78%) lactentes não estavam em aleitamento exclusivo. Os lactentes foram submetidos à inspeção … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…It was observed that the mean number of upper respiratory tract infections, including cases of otitis media, in the first two years of life was higher in the exclusively breastfed group of less than four months 22 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was observed that the mean number of upper respiratory tract infections, including cases of otitis media, in the first two years of life was higher in the exclusively breastfed group of less than four months 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Although this methodology has been used in similar studies 22,30 , it is suggested that in future studies the occurrence of both IVAS and otitis should be investigated objectively or clinically.…”
Section: Discussionmentioning
confidence: 99%
“…In the early years of life up to two years, normal ear tympanicossicular system acts differently as mass is the dominating physical feature of the ear. After this age, reaching the adult stage, there is a change in behavior which is controlled by stiffness and is better evaluated using probe frequency of 226 Hz [1]. Thus carrying out conventional tympanometry using 226Hz probe tone at early years of life may not serve of much help.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional tympanometry in infants has been used in various studies 7 8 9 10 , although the literature shows that the use of a single frequency is not sensitive enough to detect all cases of middle ear pathology, which hinders accurate diagnosis 11 12 13 14 .…”
Section: Introductionmentioning
confidence: 99%